Verification of Performance in Results-Based Financing : The Case of Panama's PSPV Program - Perazzo, Alfredo; Carpio, Carmen; Sotomayor, Renzo (World Bank, Washington, DC, 2016)
This HNP knowledge brief focuses on the key findings of the World Bank case study entitled ‘verification of performance in Results-Based Financing (RBF): the case of Panama’s health protection for vulnerable populations program (PSPV)’ (2014). The case study covers 2011 and 2012 and concentrates its analysis on data stemming from two sources: quarterly reports produced during the verification process, and interviews conducted with stakeholders involved in the implementation of the PSPV program.